The Historical Evolution of Qawaid Fiqhiyyah and Its Relevance as a Legal Maxim in the Perspective of General Law - Purnama Wahyuni; Habib Al-Rabith Naslim (Program Pascasarjana UIN Sumatera Utara Medan, 2019)
The principles of Islamic jurisprudence (Qawa'id Fiqhiyyah) play a crucial role as guidelines for Islamic law in addressing various contemporary issues amidst the limited number of texts of the Qur'an and Sunnah quantitatively. This study aims to examine the period of formation and development of the principles of Islamic jurisprudence and analyze their relationship with the concept of *legal maxim in the context of general law. Through literature study, it was found that the development of the principles of Islamic jurisprudence is divided into three main periods: the birth period (the time of the Prophet, Companions, and Tabi'in), the codification period (4th century AH to the golden age in the 8th century AH), and the refinement period culminating in the compilation of Majallat Al-Ahkam Al-Adliyyah in the 13th century AH. The analysis shows a strong relevance between the basic principles of Islamic jurisprudence and general legal principles, such as the relationship between the principle of